Effects of drying methods on quality attributes of murta (ugni molinae turcz) berries: bioactivity, nutritional aspects, texture profile, microstructure and functional properties. Issue 4 (12th November 2016) - López, Jessica; Shun Ah‐Hen, Kong; Vega‐Gálvez, Antonio; Morales, Amelia; García‐Segovia, Purificación; Uribe, Elsa
Abstract: The effects of five different drying methods: convective drying, vacuum drying, freeze‐drying, infrared‐radiation drying, and sun‐drying on various characteristic properties of murta berries from southern Chile were evaluated. The drying methods were found to have significantly different effects on the characteristics of the dried berries. Freeze‐drying process caused the least damage to the bioactive components. Over 50% loss of free total flavonoids occurred during infrared‐radiation drying, while freeze‐drying hardly affected total flavonoids in both free and bound forms. The freeze‐dried samples had the highest rehydration rate and water‐holding‐capacity, significantly different to samples of the other drying methods. Hardness was only reduced by freeze‐drying. Microstructure of the freeze‐dried samples showed similarity with that of the unprocessed berries, while noticeable cell wall collapse occurred during the other drying processes. The results obtained could be helpful in deciding for the most appropriate drying method for a desired quality of the dried murta berries. Practical Application: Drying process causes in murta berries visible physical changes that are not sufficient to evaluate quality. Nutritional aspects and biological activity that are important criteria in judging suitability of the dried murta berries as a starting raw material for developing functional foods are known to be affected by drying conditions. Therefore in this study, classic drying methods that involve a wide range of drying conditions were performed to analyse their effects on characteristic properties of dried murta berries. The data recollected are useful in the design of a drying process that best retain or even strengthen the original nutritional quality and bioactivity of the processed berries.